Analisis Sejarah Gereja di Jerman: Tradisi, Konflik, dan Pembaruan untuk Pembelajaran Iman Orang Percaya Masa Kini - Robin Stefanus Zalukhu; Malik Bambangan (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
The church tradition in Germany not only includes liturgical and theological aspects, but also serves as an important foundation for the cultural and moral identity of German society. The differences of views and clashes between church denominations and political forces have opened up space for a deeper understanding of the meaning of tolerance, reconciliation, and fidelity to the values of faith. On the other hand, the renewal of the German church reflects an effort to remain relevant in the face of the challenges of the times, such as secularism, religious pluralism, and moral crises, including through theological and liturgical reforms. This article aims to explore how the history of the church in Germany, with all its traditions, conflicts, and renewals, can be an inspiration for Christians today. The research was carried out using qualitative methods and historical approaches, using literature studies that include analysis of primary sources such as historical records, and writings of church figures, as well as secondary sources in the form of books, journals, and scientific articles. By understanding this historical journey, believers can learn about the importance of maintaining faith in the midst of changing times, strengthening unity in diversity, and reviving the spirit of spiritual renewal that is relevant to strengthen faith in today's life.